1999
DOI: 10.1023/a:1018947208597
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A non specific permeabilization of the BBB, probably related to the toxicity of the carrier, may account for the CNS penetration of dalargin associated with PBCA NP and polysorbate 80.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(42 citation statements)
references
References 13 publications
0
41
0
1
Order By: Relevance
“…While some groups have reported that nanoparticles can exert cytotoxic effects in bovine brain microvessel endothelial cells (42,43), Lockman et al (44) demonstrated that in the presence of emulsifying wax SLNs, no overall significant differences were observed in vivo for the cerebral perfusion flow. Furthermore, these authors reported that no statistically significant changes in barrier integrity, membrane permeability, or facilitated choline transport occurred in vitro in bovine brain microvessel endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…While some groups have reported that nanoparticles can exert cytotoxic effects in bovine brain microvessel endothelial cells (42,43), Lockman et al (44) demonstrated that in the presence of emulsifying wax SLNs, no overall significant differences were observed in vivo for the cerebral perfusion flow. Furthermore, these authors reported that no statistically significant changes in barrier integrity, membrane permeability, or facilitated choline transport occurred in vitro in bovine brain microvessel endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Dalargin HPLC Analysis. After separation of free dalargin from nanoparticle suspension, samples were analyzed for dalargin concentration by a HPLC method modified from that of Olivier et al 19 using an Agilent 1100 HPLC apparatus (Agilent Technologies, USA). Briefly, an isocratic reversed-phase HPLC with a Symmetry C18 5 lm column (150 3 4.6 mm 2 ) was used.…”
Section: Methodsmentioning
confidence: 99%
“…A reported high performance liquid chromatographic (HPLC) method 22 was adopted for analysis of dalargin in entrapment and release studies. HPLC analysis was carried out using the Agilent 1100 instrument (Agilent technologies, USA) with a multi-diodearray detector.…”
Section: Hplc Analysis Of Dalarginmentioning
confidence: 99%